The Analysis Of Derivational And Inflectional Morphemes In Lyric Of Songs Adele Albums - Endang S, Nurul, Drs. Sigit Haryanto, M. Hum, Dra. Siti Zuhriah Aryatmi, M. Hum (2015)
This research aimes to find out the derivational and inflectional affixes in The Songs Adele Albums. This research is descriptive qualitative research where researcher tries to find out the derivational and inflectional affix and the roots from the words in Songs Adele Albums without using statistical calculation. In this research the writer uses all of words that include prefix and suffix as the data. The data source is all the parts of words are the beginning of the lric of songs, by Adele Albums. The result of analyzing data were the derivational and inflectional affixes found in Songs Adele Albums are -er, -en, -ing, -ly, - ment, -ness as suffixes, while the inflectional affixes are -d, -s, -ed, -ing, -es, -er, - est. From the conclusion of this research, the writer suggests that to improve their mastery of vocabulary, the readers should apply the derivational and inflectional affixes by breaking the word into its elements root and affixes because from one word they can get the structure of words and they also find how the words built. By knowing the roots, the readers can build the word by themselves.